Effect of blended self-directed learning on nursing students: Quasi-experimental approach - Subhashini N Govindan; Harvinder K. D. Singh; Lee W Ling; Mahendran Sekar (Journal of Education and Health Promotion, 2023)
BACKGROUND: Higher education institutions are adapting and innovating like never before to provide highly individualized learning environments for both traditional and non-traditional students. This seismic upheaval in the higher education landscape is being observed across the world. The present study aimed to evaluate the effectiveness of a blended learning approach on nursing students' self-directed learning readiness. MATERIALS AND METHODS: This study is a quasi-experimental approach in which a non-equivalent control group was used in a post-test design. A comparison was carried out with two separate semester cohort students representing the control and intervention groups which had 24 and 30 students, respectively. This study included first-year nursing students that enrolled in a course called “Anatomy and Physiology” course of nursing education at a private university. The control group received all their teaching face-to-face, and the intervention group used information technology and prescribed activities in their online e-book. The self-directed learning readiness (SDLR) tool measures the learners' readiness in self-directed learning in both groups. This scale comprises three subscales which are “self-management,” “desire for learning,” and “self-control.” An independent-samples t-test was conducted to compare self-directed learning readiness in the control and intervention groups. Data were analyzed using IBM SPSS Statistics 25 software to measure the independent t-test. RESULTS: The self-directed readiness scores were significantly higher in the intervention group with P = 0.019. The intervention group showed a higher mean value on the subscales of self-management and self-control, which demonstrated a significant difference with P values of 0.018 and 0.028, respectively. The subscale desire for learning was insignificant with a P value of 0.166. CONCLUSION: This study concluded that the overall results demonstrate that incorporating blended learning using e-books for anatomy and physiology courses in nursing education can contribute to students' readiness for self-directed learning. Specifically, the blended learning teaching and learning strategy had a positive impact on nursing students' capacity for self-management and self-control.